Mutants at Ser277 of Xenopus cdc2 protein kinase induce oocyte maturation in the absence of the positive regulatory phosphorylation site Thr161. - Pickham, K M (1994)
The cdc2 protein kinase is an important regulatory protein for both meiosis and mitosis. Previously, we demonstrated that simultaneous mutation of Thr14-->Ala14 and Tyr15-->Phe15 in the Xenopus cdc2 protein results in an activated cdc2 mutant that induces maturation in resting oocytes. In addition, we confirmed the importance of the positive regulatory phosphorylation site, Thr161, by demonstrating that cdc2 mutants containing additional mutations of Thr161-->Ala161 or Glu161 are inactive in the induction of oocyte maturation. Here, we have analyzed the importance of an additional putative cdc2 phosphorylation site,Ser277. Single mutation of Ser277-->Asp277 or Ala277 had no effect on activity, and these mutants were unable to induce Xenopus oocyte maturation. However, the double mutant Ala161/Asp277 was capable of inducing oocyte maturation, suggesting that mutation of Ser277-->Asp277 could compensate for the mutation of Thr161-->Ala161. The Asp277 mutation could also compensate for the Ala161 mutation in the background of the activating mutations Ala14/Phe15. Although mutants containing the compensatory Ala161 and Asp277 mutations were capable of inducing oocyte maturation, these mutant cdc2 proteins lacked detectable in vitro kinase activity. Tryptic phosphopeptide mapping of mutant cdc2 protein and comparison with in vitro synthesized peptides indicated that Ser277 is not a major site of phosphorylation in Xenopus oocytes; however, we cannot rule out the possibility of phosphorylation at this site in a biologically active subpopulation of cdc2 molecules. The data presented here, together with prior reports of Ser277 phosphorylation in somatic cells, suggest an important role for Ser277 in the regulation of cdc2 activity. The regulatory role of Ser277 most likely involves its indirect effects on the nearby residue Arg275, which participates in a structurally important ion pair with Glu173, which lies in the same loop as Thr161 in the cdc2 protein.